THE GRAMMATICAL CATEGORY OF NUMBER IN THE GERMAN LANGUAGE - Azamatova, Gulnoza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article explores the grammatical category of number in the German language, focusing on the ways in which number is expressed, including its syntactic, morphological, and semantic aspects. The study of the German number system reveals its complexity, with distinctions between singular, plural, and dual forms, as well as the intricacies of their usage in both nominal and verbal structures. The paper reviews key literature on the topic, examining how number affects sentence structure, word agreement, and overall communicative function in German. Special attention is paid to the historical development of number morphology and its contemporary usage.